Improved Fault-Tolerant Aggregate Signatures. (29th March 2019) - Wang, Gaoli; Cao, Zhenfu; Dong, Xiaolei
Abstract: Fault-tolerant aggregate signatures allow the verification algorithm to recognize and verify all the valid individual signatures in an aggregate signature. However, in ordinary aggregate signature schemes, if there is a single faulty individual signature in the valid aggregate, the whole aggregate will be invalid. This will make great difficulties in many applications including secure logging and batch verification in vehicular ad hoc network et al. In this paper, inspired by the finite set theory called uniform ( k, n )-set proposed by Cao, we put forward a novel fault-tolerant aggregate signature scheme. Our new scheme is more efficient compared with previous fault-tolerant aggregate signature scheme based on cover-free family. It is noted that our scheme is quite easy to be implemented in the real scenario.